Chapter Discorsi intrecciati: David Sassoli e il rinnovamento del progetto europeo - Paolinelli, Lui´sa M. Antunes (Libere carte, 2023)
In his last speech as President of the European Parliament, on 16 December 2022, addressed to the heads of state of the European Union and entitled "Europe must show allegiance to its citizens", David Sassoli underlines the importance of thinking about the Europe of the future. Bearing in mind the history and memory of the continent, the roots of the Euroean culture and its long traditions of humanistic and scientific knowledge, he presents three axes of development - innovation, protection and dissemination - for a Europe that must be thought of as a project, dynamic, hopeful, young spirited and faithful to its humanist and democratic basis.